Split-face histological and biochemical evaluation of tightening efficacy using temperature- and impedance-controlled continuous non-invasive radiofrequency energy. (3rd April 2017) - Boisnic, Sylvie; Divaris, Marc; Branchet, Marie-Christine; Nelson, Andrew A.
ABSTRACT: Background : Bipolar radiofrequency (RF) is capable of heating dermal collagen fibers and inducing skin tightening by collagen remodeling.Objective : To substantiate safety and improvement of skin laxity following skin heating with a novel temperature- and impedance-controlled non-invasive radiofrequency (RF) device by histological and biochemical evaluations.Methods : A split-face study was performed on 4 subjects who underwent 8 weekly RF sessions on one side of their face, leaving the other side an untreated control and then underwent facelift procedure. Clinical evaluation by photographs was done prior to the surgical procedure. Ex vivo fragments were harvested from both sides and compared. Morphometric analysis of dermal collagen fibers, collagen synthesis, and elastin synthesis evaluations were compared in triplicates.Results : Facial skin tightening was apparent in split-face photographs. A significant increase of 7.9% in dermal collagen content, and a significant increase of 34.7% in collagen synthesis were demonstrated in the treated samples. No statistically significant effect on elastin synthesis was detected.Conclusions : Skin tightening following treatment with non-invasive RF has proven histologically and biochemically to derive from increase in dermal collagen synthesis and content.